2017
DOI: 10.1259/bjr.20160370
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different contouring definitions of the rectum as organ at risk (OAR) and dose–volume parameters predicting rectal inflammation in radiotherapy of prostate cancer: which definition to use?

Abstract: MN and RMH contributed to the conception, design, analysis and interpretation of data and helped with the final approval of the version to be published. MN, RMH and NT helped with the drafting of the article. WB and MB contributed to the statistics of the main study. DW contributed to the acquisition of data. AK contributed to the statistics of pre-study. NT helped with the planning and implementation of radiotherapy.Objective: The objective of this retrospective planning study was to find a contouring definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Prior data examining truncation of rectal contours is limited. Retrospectively contouring 163 primary/salvage EBRT prostate patients, Nitsche et al 18 examined 3 different rectal definitions (chosen from 13 based on DVH heterogeneity): RTOG definition, PTV ± 1 cm, PTV ± 0 cm. No relationship was seen between various DVH parameters and worst late rectal inflammation G1+ (Common Terminology Criteria for Adverse Events).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior data examining truncation of rectal contours is limited. Retrospectively contouring 163 primary/salvage EBRT prostate patients, Nitsche et al 18 examined 3 different rectal definitions (chosen from 13 based on DVH heterogeneity): RTOG definition, PTV ± 1 cm, PTV ± 0 cm. No relationship was seen between various DVH parameters and worst late rectal inflammation G1+ (Common Terminology Criteria for Adverse Events).…”
Section: Discussionmentioning
confidence: 99%
“…The choice of truncations to take forward to toxicity analysis (0 and 2 cm) was made pragmatically based on prior work in the field. 18 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In RT, differences in OAR volumes do not always translate into large dose differences [9] , [21] although compliance to trial protocols have been reported to be compromised due to incorrect delineations [2] . We found in our data that autosegmented rectal volumes, irrespective of algorithm version, were overall closer to the manually-delineated uncurated clinical rectal volumes (Δ≈0.5–1 cm 3 ) than to the manually-delineated curated rectal volumes (Δ≈1-3 cm 3 ), with the larger differences typically generated by the smaller-sized training datasets.…”
Section: Discussionmentioning
confidence: 99%
“…In general, overestimated dose for OARs brings the dose distributions to the safer side, however, underdosage of tumours may be a consequence if the OAR is directly adjacent to the planning target volume and unintendedly included in the high-dose region on the basis of an incorrectly-defined volume [18] . Furthermore, variations in rectum volumes and the impact on rectal toxicity modelling has been investigated in a retrospective study where the same rectum definition as used for our curated volumes was included as one of 13 investigated OAR definitions [21] . This study found that the more distinct differences in DVH shapes between the OAR definitions related to volumes of 60–110 cm 3 , mean doses of 35–50 Gy, and maximum doses of 70–73 Gy (n = 163; 3D-CRT primary and salvage prostate cancer treatments; prescribed dose = 67–76 Gy).…”
Section: Discussionmentioning
confidence: 99%